2013
DOI: 10.4049/jimmunol.1300053
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Atherosclerosis in TIPE2-Deficient Mice Is Associated with Increased Macrophage Responses to Oxidized Low-Density Lipoprotein

Abstract: Atherosclerosis has been widely recognized as an inflammatory disease of the arterial wall in which macrophages play a major role. Yet, how macrophage-mediated pathology is regulated during atherosclerosis is poorly understood. TNF-α–induced protein 8–like 2 (TIPE2, also known as TNFAIP8L2) is highly expressed in resting macrophages and can negatively regulate inflammation through inhibiting immune receptor signaling. We report in this article that TIPE2 plays a crucial atheroprotective role likely by regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 35 publications
5
46
0
Order By: Relevance
“…75 In addition, TIPE2 regulates macrophage responses to oxidized low-density lipoproteins (ox-LDL); TIPE2-deficient macrophages produced more oxidative stress and inflammatory cytokines, with associated increases in JNK, NF-κB, and p38 signaling. 76 In conjunction with this finding, TIPE2 deficiency in the bone marrow increased atherosclerosis formation in Ldlr − / − mice fed a high-fat diet, and ox-LDL was found to downregulate TIPE2 mRNA expression. 76 Interestingly, atorvastatin seems to potentiate the LPS-mediated expression of TIPE2, with downstream decreases in inflammatory mediators, including NO synthase and NF-κB.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 70%
See 1 more Smart Citation
“…75 In addition, TIPE2 regulates macrophage responses to oxidized low-density lipoproteins (ox-LDL); TIPE2-deficient macrophages produced more oxidative stress and inflammatory cytokines, with associated increases in JNK, NF-κB, and p38 signaling. 76 In conjunction with this finding, TIPE2 deficiency in the bone marrow increased atherosclerosis formation in Ldlr − / − mice fed a high-fat diet, and ox-LDL was found to downregulate TIPE2 mRNA expression. 76 Interestingly, atorvastatin seems to potentiate the LPS-mediated expression of TIPE2, with downstream decreases in inflammatory mediators, including NO synthase and NF-κB.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 70%
“…76 In conjunction with this finding, TIPE2 deficiency in the bone marrow increased atherosclerosis formation in Ldlr − / − mice fed a high-fat diet, and ox-LDL was found to downregulate TIPE2 mRNA expression. 76 Interestingly, atorvastatin seems to potentiate the LPS-mediated expression of TIPE2, with downstream decreases in inflammatory mediators, including NO synthase and NF-κB. 77 TIPE3 is an oncogenic transfer protein of lipid second messengers TIPE3 is the most recently investigated TIPE family member, and only a few articles have been published regarding this protein.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 70%
“…TNFAIP8L2 (TIPE2), the tumor necrosis factor (TNF)-α-induced protein 8 (TNFAIP8, TIPE) like 2, is a member of the TNFAIP8 family that plays important roles in controlling inflammation and tumorgenesis by suppressing RAS signaling [7][8][9][10]. Its deficiency in 129/J mice causes fatal inflammatory diseases [8] and abnormal expression in humans is associated with many kinds of diseases, such as hepatocellular carcinoma [7,10], stroke [11], HBV infection [12] and atherosclerosis [13,14]. Our previous studies showed that TIPE2 plays atheroprotective roles by negatively regulating ox-LDL-induced inflammatory responses in macrophages [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Its deficiency in 129/J mice causes fatal inflammatory diseases [8] and abnormal expression in humans is associated with many kinds of diseases, such as hepatocellular carcinoma [7,10], stroke [11], HBV infection [12] and atherosclerosis [13,14]. Our previous studies showed that TIPE2 plays atheroprotective roles by negatively regulating ox-LDL-induced inflammatory responses in macrophages [13,14]. Furthermore, TIPE2 could inhibit neointima formation by regulating phenotypic switching of VSMCs during atherogenesis [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation